Dari Jakarta ke Penajam: Membangun Kota, Mengonstruksi Makna dan Budaya - Wahyuddin, Wahyuddin (Jurnal Sejarah Indonesia, 2023)
This article discusses plans to move Indonesia's capital city to the Penajam area, North Paser, East Kalimantan. Reading the history of the relocation of the capital city and the politics of capital city spatial planning both during the colonial and post-independence periods, it is clear that symbolic aspects in space play an important role in representing culture as well as constructing the culture desired by the government. Based on data obtained through the official government website, it appears that the current transfer and spatial planning of IKN on the island of Kalimantan is also basically a cultural policy of the government, namely an effort to create a national capital that reflects a national identity that transcends all barriers of ethnic identity and another primordial identity.